Dual-triggered nanoaggregates of cucurbit[7]uril and gold nanoparticles for multi-spectroscopic quantification of creatinine in urinalysis. Issue 21 (27th April 2020) - Chio, Weng-I Katherine; Moorthy, Suresh; Perumal, Jayakumar; U. S., Dinish; Parkin, Ivan P.; Olivo, Malini; Lee, Tung-Chun
Abstract : A novel nanosensing platform was developed for the quantitative detection of creatinine of clinically relevant concentrations via UV-Vis spectroscopy and surface-enhanced Raman spectroscopy. Abstract : Plasmonic nanocomposites of cucurbit[7]uril (CB7) and gold nanoparticles (Au NPs) have been optimised and applied to rapidly detect and quantify creatinine (CRN) of clinically relevant levels in urinalysis. The in situ formation of plasmonic nanocomposites via aqueous self-assembly is mediated by a combination of the portal binding of CB7 and the electrostatic effects of CRN molecules, allowing independent spectral signatures to be extracted from the same sample solution using surface-enhanced Raman spectroscopy (SERS) and UV-Visible spectroscopy. Meanwhile the formation of host–guest complexes between CB7 and CRN allows quantification of CRN in highly diluted synthetic urine by localising CRN at or in close proximity to the plasmonic hotspots within the Au NP:CB7 nanoaggregates, which enables highly reproducible SERS signals (within 5% error) with a sub-μM detection limit of 12.5 ng mL −1 (111 nM) and has tolerance against the presence of proteins and other biomolecules in a complex matrix. Our nanobiosensing material platform demonstrates the potential to be extended to other in-field applications.